Auricular chondritis and diffuse proliferative glomerulonephritis in primary Sjögren's syndrome. Issue 8 (August 1989) - Rodriguez, M A; Tapanes, F J; Stekman, I L; Pinto, J A; Camejo, O; Abadi, I
Abstract : Bilateral auricular inflammation with histological changes of relapsing polychondritis was observed in a female patient with primary Sjögren's syndrome. This was accompanied by rapidly progressive renal insufficiency due to diffuse proliferative glomerulonephritis. To our knowledge this is the first well documented case of primary Sjögren's syndrome associated with chondritis and glomerulonephritis, further emphasising the wide spectrum of extraglandular manifestations in this autoimmune disorder.